6t+8=33+t

Simple and best practice solution for 6t+8=33+t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t+8=33+t equation:


Simplifying
6t + 8 = 33 + t

Reorder the terms:
8 + 6t = 33 + t

Solving
8 + 6t = 33 + t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.
8 + 6t + -1t = 33 + t + -1t

Combine like terms: 6t + -1t = 5t
8 + 5t = 33 + t + -1t

Combine like terms: t + -1t = 0
8 + 5t = 33 + 0
8 + 5t = 33

Add '-8' to each side of the equation.
8 + -8 + 5t = 33 + -8

Combine like terms: 8 + -8 = 0
0 + 5t = 33 + -8
5t = 33 + -8

Combine like terms: 33 + -8 = 25
5t = 25

Divide each side by '5'.
t = 5

Simplifying
t = 5

See similar equations:

| 3x+4y-6y^2+90=0 | | 35x^4-28x^7=0 | | 3x+3=x+13 | | 4x=2x+40 | | x+18=24 | | 600=30d | | 2x-3[4-(3x-7)]= | | 10-11d=-5d-4 | | 5n+4=n+24 | | 9z/7=-30 | | 5(x+9)=x+69 | | 9x^2+24x+16= | | d^2+10d-684.5217391=0 | | 8=-4b+6b | | -16x^2-8x+24=0 | | -300-(-4x)=-8x | | -21x^2-21x+42=0 | | -16t^2+32t+20=0 | | 3x-y-7=0 | | 6x=2x+14 | | 5x^2-13x-28=0 | | 8x+15=4x-5 | | y=-0.5x^2+4.5x | | 78x^4+143x^3-39x^2-26=0 | | 0=20a^2-4a | | 18x^2-39x+15=0 | | 3n-1=11 | | 6x^2+19+3=0 | | d^2+10d-1200=0 | | x=3x-70 | | 10x^4-30x^3-530x^2-90=0 | | 7x+5=2x-13 |

Equations solver categories